2004
DOI: 10.1002/pbc.20161
|View full text |Cite
|
Sign up to set email alerts
|

Tetrasomy 21 transient leukemia with aGATA1 mutation in a phenotypically normal trisomy 21 mosaic infant: Case report and review of the literature

Abstract: Infants with constitutional trisomy 21 are at increased risk of developing transient and acute megakaryoblastic leukemia (AMKL). Mutations in GATA1 have been identified in trisomy 21 patients with AMKL, and this lesion is thought to be an initial event by virtue of its presence during transient leukemia. Transient leukemia is also observed in phenotypically normal infants albeit much less commonly so. Almost all these infants are mosaic for trisomy 21, and the clinical course of transient leukemia recapitulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Unfortunately, clinical samples were not obtained except UPN5; we could not reveal the correlation between the presence of GATA1 mutations and the good prognosis in our series. Sandoval et al [18] reported a patient of TAM with GATA1 mutation in a mosaic DS. The same interpretations would be made concerning GATA1 mutations in mosaic DS and AMKL.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, clinical samples were not obtained except UPN5; we could not reveal the correlation between the presence of GATA1 mutations and the good prognosis in our series. Sandoval et al [18] reported a patient of TAM with GATA1 mutation in a mosaic DS. The same interpretations would be made concerning GATA1 mutations in mosaic DS and AMKL.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3] Children with DS have a 1 in 500 chance of developing acute megakaryoblastic leukemia (AMKL), 4-6 and 19% of DS (or trisomy 21 mosaic) neonates who are diagnosed with TL develop AMKL within 4 years. 3,7 Somatic mutations of GATA1 are found in almost all cases of DS or mosaic trisomy 21-associated TL and AMKL. 8 GATA1 mutations have not been detected in healthy children without DS, in DS children with other types of leukemia, or in AMKL cells of non-DS/non-trisomy 21 mosaic children, with the exception of a single case of adult AMKL without DS or acquired trisomy 21.…”
mentioning
confidence: 99%
“…These cases highlight the significance of trisomy 21 as the causative cytogenetic alteration. However, genetic status of GATA1 has been rarely characterized and five such cases have been reported [8][9][10][11][12]. This patient showed G-C substitution in the boundary between exon 2 and intron 2 of GATA1.…”
Section: Discussionmentioning
confidence: 84%
“…In such cases, the status of GATA1 has been rarely characterized [8][9][10][11][12]. We present a cytogenetically normal neonate with TAM who showed acquired trisomy 21 and somatic mutation of GATA1 exon 2.…”
Section: Introductionmentioning
confidence: 91%